Peran Guru melalui Pembelajaran Sejarah Lokal dalam Mempersiapkan Generasi Tangguh - Nino Melkias Mailani; Leo Agung S; Deny Tri Ardianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
History learning is the approach of a teacher in order to introduce students to local wisdom that is around them. The aim is to find out the role of teachers through learning local history and to find out the obstacles and efforts of teachers in preparing the Tangguh Generation. The method used is a qualitative method. The results of the study indicate that the history teacher acts as a guide who acts like a parent, assists, directs, and motivates students in learning local history. The role of the history teacher is as a stimulus for students' creativity by providing variations in local history learning to make it more interesting, acting as a seeker to enrich knowledge by constantly seeking local historical sources and as an authority. The obstacles and efforts of teachers in developing the character of class X Social Studies students through local history learning at SMA Kristen 1 Soe are: (1) The difficulty of history teachers in adjusting the character to be achieved with the material to be taught. (2) The history teacher has difficulty understanding the psychological condition of students who tend to be passive. (3) Lack of supervision of students after being outside school.